Integrating Ecological Literacy into Strategic Planning Frameworks for Adult Education Institutions: A Theoretical and Policy Analysis - Omang, Theresa Nkim; Akom, Eki Rose; Odu, Annastasia Odu (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
As the global climate crisis intensifies, adult education institutions face growing responsibility to incorporate environmental sustainability into their strategic planning processes. This paper explores the theoretical and policy-based rationale for integrating ecological literacy into education administration planning within the context of environmental adult education. Drawing on key concepts from systems theory, transformative learning, and sustainability education, the paper argues that ecological literacy—understood as the capacity to perceive and act with awareness of the interdependence between human and ecological systems—should be a guiding principle in the long-term strategic visions of adult learning institutions. The study critically analyzes the limitations of conventional planning models such as SWOT analysis and linear logic frameworks, which often fail to account for ecological interconnectivity and long-term environmental implications. Through a conceptual review of strategic planning literature and an interpretive analysis of relevant policy frameworks, the paper proposes a model for “ecologically-informed strategic planning.” This model emphasizes adaptive systems thinking, participatory governance, and the embedding of sustainability outcomes in institutional missions and curricula. The paper concludes that reimagining adult education planning through the lens of ecological literacy can foster more resilient, responsive, and ethically grounded institutions capable of preparing adults for the complex ecological challenges of the 21st century